Challenges in Measuring AMH in the Clinical Setting - Li, Hang Wun Raymond; Robertson, David Mark; Burns, Chris; Ledger, William Leigh (Frontiers in Endocrinology, 2021)
Serum anti-Mullerian hormone (AMH) is a widely used marker of functional ovarian reserve in the assessment and treatment of infertility. It is used to determine dosing of gonadotropins used for superovulation prior to in vitro fertilisation, as well as to determine the degree of damage to ovarian reserve by cytotoxic treatments such as chemotherapy. AMH is also now used to predict proximity to menopause and potentially provides a sensitive and specific test for polycystic ovarian syndrome. Twenty one different AMH immunoassay platforms/methods are now commercially available. Of those compared, the random-access platforms are the most reliable. However, to date there has not been an agreed common international AMH reference preparation to standardise calibration between the various immunoassays. Recently, a purified human AMH preparation (code 16/190) has been investigated by the World Health Organisation as a potential international reference preparation. However, this was only partially successful as commutability between it and serum samples was observed only in some but not all immunoassay methods. Development of a second generation reference preparation with wider commutability is proposed.